Biallelic mutations in the LPAR6 gene causing autosomal recessive wooly hair/hypotrichosis phenotype in five Pakistani families. (11th May 2019) - Khan, Ghulam M.; Hassan, Noor; Khan, Niamatullah; Humayun, Muhammad; Khan, Kafaitullah; Khaliq, Samira; Rehman, Fazal U.; Ahmed, Sheikh; Shah, Khadim; Khan, Sher A.; Muhammad, Noor; Wali, Abdul; et al.
Abstract: Background: Autosomal recessive wooly hair/hypotrichosis is an inherited disorder of hair characterized by less dense, short, and tightly curled hair on the scalp and sometimes less dense to complete absence of eyebrows and eyelashes. Autosomal recessive wooly hair/hypotrichosis phenotypes are mostly associated with pathogenic sequence variants in LIPH and LPAR6 genes. Methods: To find out the molecular basis of the disease, five families with autosomal recessive wooly hair/hypotrichosis were recruited for genetic analysis. Direct Sanger sequencing of LIPH and LPAR6 genes was carried out using BigDye chain termination chemistry. P2RY5 protein homology models were developed to study the effect of mutation on protein structure in a family having novel mutation. Results: Sanger sequencing revealed a novel homozygous missense mutation (c.47A>T) in the LPAR6 gene in family A, while recurrent mutation (c.436G>A) was detected in the rest of the four families (B‐E). Protein homology models for both native and mutant P2RY5 protein were developed to study the difference in subtle structural features because of Lys16Met (K16M) mutation. We observed that P2RY5K16M mutation results decrease in the number of ionic interactions detrimental to the protein stability. Protein modeling studies revealed that the novel mutation identified here decreased the number of ionic interactions by affecting physicochemical parameters of the protein, leading to an overall decrease in protein stability with no major secondary structural changes. Conclusion: The molecular analysis further confirms the frequent involvement of LPAR6 in autosomal recessive wooly hair/hypotrichosis, while the bioinformatic study revealed that the missense mutation destabilizes the overall structure of P2RY5 protein.